2003
DOI: 10.1002/polb.10436
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy resin/poly(ϵ‐caprolactone) blends cured with 2,2‐bis[4‐(4‐aminophenoxy)phenyl]propane. II. Studies by Fourier transform infrared and carbon‐13 cross‐polarization/magic‐angle spinning nuclear magnetic resonance spectroscopy

Abstract: Crystalline thermosetting blends composed of 2,2′‐bis[4‐(4‐aminophenoxy)phenyl]propane‐crosslinked epoxy resin (ER) and poly(ϵ‐caprolactone) (PCL) were investigated by means of Fourier transform infrared (FTIR) spectroscopy and high‐resolution solid‐state NMR spectroscopy. FTIR investigations indicated that there were specific intermolecular interactions between ER and PCL and that the intermolecular hydrogen‐bonding interactions were weaker than the self‐association in pure epoxy. The intermolecular hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…86,87 Results showed that PCL is partially miscible in epoxy amine mixture due to the H bond formation between ester oxygen atoms and hydroxyl or amine moieties of epoxy-amine system. However, depending on the mixture nature, phase separation can start at a certain content of PCL, while a fully homogeneous PCL/epoxy blends can be obtained with a reasonable amount of PCL, as showed Zheng et al 88 Some other examples of modifiers exist as poly(vinyl acetate), 89 poly(etherimide), 90 more complex structures, such as poly(phthalazinone ether nitrile ketone), 91 and even poly(styrene), 92 which cannot form H bonds but can interact with π-bonds with aromatic epoxy and amine reactants, allowing initial miscibility.…”
Section: Addition Of Modifier Prepolymermentioning
confidence: 94%
“…86,87 Results showed that PCL is partially miscible in epoxy amine mixture due to the H bond formation between ester oxygen atoms and hydroxyl or amine moieties of epoxy-amine system. However, depending on the mixture nature, phase separation can start at a certain content of PCL, while a fully homogeneous PCL/epoxy blends can be obtained with a reasonable amount of PCL, as showed Zheng et al 88 Some other examples of modifiers exist as poly(vinyl acetate), 89 poly(etherimide), 90 more complex structures, such as poly(phthalazinone ether nitrile ketone), 91 and even poly(styrene), 92 which cannot form H bonds but can interact with π-bonds with aromatic epoxy and amine reactants, allowing initial miscibility.…”
Section: Addition Of Modifier Prepolymermentioning
confidence: 94%
“…Initiation Mechanism Reference [59] Polymers 2022, 14, x FOR PEER REVIEW 2 of 16 have been used as epoxy modifiers and reported in the literature, including polyetherimide (PEI) [25], polymethylmethacrylate [26], polyethylene oxide [27], polycarbonate [28], and poly(ε-caprolactone) (PCL) [17,19,[29][30][31][32][33][34][35][36][37][38].…”
Section: Il Typementioning
confidence: 99%
“…The use of different curing agents and PES with different molecular weights resulted in varying morphologies. Many other thermoplastic polymers have been used as epoxy modifiers and reported in the literature, including polyetherimide Polymers 2022, 14, 2679 2 of 14 (PEI) [25], polymethylmethacrylate [26], polyethylene oxide [27], polycarbonate [28], and poly(ε-caprolactone) (PCL) [17,19,[29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, thermosetting polymer blends have attracted considerable interest. A number of thermosetting blends, in which one component is a crystallizable linear homopolymer and another is highly crosslinked, have been proved to be miscible or partially miscible by Guo and coworkers1–15 and by other researchers 16–22. It has been shown that miscibility, that is, the ability to form a homogeneous single phase in the melt and/or in the amorphous state, can exist between the components for crosslinked blends with hydrogen‐bonding interactions.…”
Section: Introductionmentioning
confidence: 99%